Nonarteritic Ischemic Optic Neuropathy Due to the Increased Intraocular Pressure During Cataract Surgery: A Case Report - Sadık Etka Bayramoğlu; Nihat Sayın; Mehmet Erdoğan; Dilbade Yıldız Ekinci (Haseki Tıp Bülteni, 2017)
A 46-year-old patient diagnosed with rheumatoid arthritis underwent cataract surgery for a subcapsular cataract. Perioperative intraocular pressure (IOP) increased after two sideport incisions. Despite administration of 300 cc of 20% mannitol, the elevated IOP persisted for 30 minutes. IOP decreased after pressing the posterior surface of the sideports with a 25 G cannula. The other steps of cataract surgery and intraocular lens implantation were performed uneventfully. On the first postoperative day, the diagnosis of nonarteritic ischemic optic neuropathy (NAION), which was thought to be the result of increased IOP in the perioperative period, was recorded. Cataract surgeons keep in mind and urgently perform simple maneuvers to lower IOP in order to prevent unexpected vision-threatening complications, such as NAION. In addition, for patients who have a crowded optic nerve head with a small cup-to-disc ratio or a previous episode of NAION in the other eye, perioperative and postoperative ocular pressure must be attentively managed.